Pemodelan Sebaran Polutan TSP Dari Sumber Emisi Point Source Pada Industri Kimia Dengan Bahan Bakar Compacted Natural Gas - Shifa, Farah Alya Cahya; Adzillah, Wilma Nurrul; Fauzie, Azis Kemal (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The growth of industry in Karawang Regency impacts the increase in burning activities in the production process, which has the potential to become a source of air pollution. These activities generate pollutants that are hazardous to humans and ecosystems. This research aims to analyze the meteorological factors influencing the distribution patterns of TSP pollutant concentrations, as well as to map the distribution patterns resulting from burning activities in the chemical industry using AERMOD View, during the dry and rainy seasons, which will produce the concentration values of pollutants received by receptors. The method used is quantitative, using an air pollutant dispersion modeling approach using AERMOD View. Secondary data consists of emission data, meteorological data, and topographic data. Data analysis was performed by comparing the AERMOD View modeling results across seasons. Furthermore, concentration values were compared with Ambient Air Quality Standards referred to in Government Regulation No. 22 of 2021. Based on the research, the combination of meteorological factors, wind direction, and wind speed are the main parameters. The pattern of pollutant dispersion is determined by the interaction between wind direction, distance, receptor elevation, when combined with the physical characteristics of the chimney and the amount of emission load released by the emission source, it will determine the magnitude of the pollutant concentration received by the receptor.